If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4 + -1x = 2x + 6 Reorder the terms: -4 + 3x + -1x = 2x + 6 Combine like terms: 3x + -1x = 2x -4 + 2x = 2x + 6 Reorder the terms: -4 + 2x = 6 + 2x Add '-2x' to each side of the equation. -4 + 2x + -2x = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 + 0 = 6 + 2x + -2x -4 = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 = 6 + 0 -4 = 6 Solving -4 = 6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| b-10=-29 | | ax-7n=v | | 4x-2x+6=3x+8-7 | | 10+a=-8 | | 8(n-8)=-152 | | 2(x-7)=x+4 | | -6(x-3)=-72 | | v-4/3(3.14)(21)^ | | 3(2x+4)=2(x-12) | | 16b=160 | | (y^2-2xy)dx+(3x^2-xy^2)dy=0 | | 20+13y=410 | | x/19=15/19 | | v=4.19(21) | | 3x^7+18=-15 | | 116=5w+16 | | 4x-2+6=3x+8-17 | | 3-6x+8x=19 | | 4x-2x+6=3x+8-17 | | 44+y=82 | | 10/22=y/33 | | 44+y=262 | | 1/22=y/33 | | s*7+39=186 | | 1-/22=y/33 | | -3x-4=6x-8 | | (x^3y^2/x^4y^2)^2 | | 3x-2=5+5x | | a+y=b | | 4x-y+3z=0 | | 4a-(3a-2)=2(3a-2) | | e^2k=10 |